The Myanmar Rohingyas: Challenges faced by the ‘refugee’ community in Malaysia, 2014-2016 / Azlinariah Abdullah - Azlinariah, Abdullah (2019)
The purpose of this study is to highlight the challenges of social integration among the Rohingyas in Malaysia as refugees, and the extent to which the direct and indirect challenges have played a role in the process of social and cultural integration. This research, based on interviews with the Rohingyas living in Malaysia, focuses on their everyday lives as refugees. The ethnographic research design, combining semi-structured interviews provides an opportunity to analyze social relations in Malaysia. The problems and challenges of integration as refugees and their survival as a Muslim minority community from Myanmar are also discussed, based on fieldwork involving observation in some Rohingya urban settings. Library sources are used to share an overview of the Rohingyas. Findings are based on earlier research, interviews with experts on Rohingya issues, and the Rohingya communities in Malaysia. Based on case studies, the thesis concludes with a recommendation for successfully integrating Rohingya refugees in Malaysia and a policy that can be reviewed or amended. The analysis of the Rohingyas draws on the conceptual framework of Survival Migration, by Alexander Betts and Alastair Ager and Alison Strang, authors of Understanding Integration. This research indicates that the Rohingyas in Malaysia are still struggling to find their place in the host country. However, many of these refugees are coping well in Malaysia, though there is still much that could be done by local government and international bodies in ensuring the continued survival as refugees. This research also demonstrates the ambiguous status of the Rohingyas as a serious complication in their daily lives, and provides a strong basis for understanding what is happening to the Rohingyas and for determining their root problems. The findings indicate that the mastery of language, employment and the ability to establish social networks with local people are important factors in achieving integration. In addition, there is a need to educate the host community about refugees and policies must be reviewed and amended in terms of education and employment to ensure the social inclusion and successful integration of the Rohingya refugees in Malaysia.